Freedom: East and West - Shaw, Jaysankar L. (Sophia, 2011)
This paper explains some of the uses of the word ‘freedom’ in Western as well as in Indian philosophy. Regarding the psychological concept of freedom or free will, this paper focuses on the distinction between fatalism, determinism, types of compatibilism, and libertarianism. Indian philosophers, by and large, are compatibilists, although some minor systems, such as Śākta Āgama, favor a type of libertarianism. From the Indian perspective the form of life of human beings has also been mentioned in the discussion of free will. Regarding metaphysical freedom, I discuss the views of the Bhagavad Gītā and Swami Vivekananda in Sect. III. K.C. Bhattacharyya, a neo-Advaita Vedāntin, has discussed degrees of freedom of the subject at several levels. According to him, spiritual progress lies in the progressive realization of the freedom of the subject. I compare his view with the classical Advaita concept of freedom. I have also addressed the question of whether freedom from suffering can be realized at social and global levels. In this context I have mentioned some of the interpretations of the great saying ‘I am Brahman,’ and how freedom can be realized at the global level by using the Advaita concept of ‘oneness.’